Characteristic study of a novel compact Solar Thermal Facade (STF) with internally extruded pin–fin flow channel for building integration. (15th April 2016) - Shen, Jingchun; Zhang, Xingxing; Yang, Tong; Tang, Llewellyn; Cheshmehzangi, Ali; Wu, Yupeng; Huang, Guiqin; Zhong, Dan; Xu, Peng; Liu, Shengchun
Highlights: A novel compact STF with internally extruded pin–fin flow channel is proposed. Thermal performance of the STF is characterized in different operation modes. This STF is with simple structure, low cost and high feasibility in building design. Such STF can achieve better thermal performance as conventional ones. Abstract: The fully building integrated Solar Thermal Facade (STF) systems can become potential solutions for aesthetics architectural design, as well as for the enhancement of energy efficiency and reduction of operational cost in the contemporary built environment. As a result, this article introduces a novel compact STF with internally extruded pin–fin flow channel that is particularly suitable for the building integration. A dedicated simulation model was developed on basis of the heat transfer and the flow mechanics. A prototype of this STF was fabricated and then it was tested under a series of controlled environmental conditions. The experimental validation illustrated a good agreement with the simulation results, indicating the established model was able to predict the STF's thermal performance at a reasonable accuracy (i.e. mean deviation of less than 5.46%). The impacts of several operational parameters, i.e. equivalent solar radiation, air temperature, air velocity, water mass flow rate and inlet water temperature, on the STF thermal performance were then discussed respectively. Given the baseline testing condition, the collector efficiency factor F ′ is almost 0.9930, leading to a relatively high nominal thermal efficiency at about 63.21%, which demonstrates such STF, with simpler structure, lower cost and higher feasibility in architectural design, can achieve an equivalent or better thermal performance than recent bionic STF or the conventional ones. It is also concluded that the thermal efficiency varies proportionally with solar radiation, air temperature, and mass flow rate of water, but oppositely to air velocity and inlet water temperature. A sharp decreasing trend of this STF's thermal efficiency against the ( Tin  −  Ta )/ I was observed under the given operational conditions, which indicates current STF design is only suitable for pool heating, domestic hot water and radiant space heating in areas/climates with warm ambient air temperature and sufficient solar radiation. The overall research results are beneficial for further design, optimization and application of such STF in various solar driven systems, including the provision of hot water, space heating/cooling, increased ventilation, or even electricity in buildings. Such STF technology has the potential to boost the building energy efficiency and literally turn the envelope into an independent energy plant, creating the possibility of solar-thermal technologies deployment in high-rise buildings.